Early Learning Redefined: Analyzing the Pedagogical Shifts in Pre-Primary Education in NEP 2020 - Bhoi, Chandrasekhar; Patra, Bhagyashree (PT. Riset Press International, 2025)
The National Education Policy (NEP) 2020 marks a significant turning point in India's early childhood education landscape. Recognizing the critical importance of the formative years (ages 3–8), the policy proposes a holistic, integrated, and developmentally appropriate pedagogical approach that moves away from rote memorization and narrow academic focus. Instead, NEP 2020 emphasizes foundational literacy and numeracy, play-based and experiential learning, and child-centered teaching strategies. This review article critically examines the pedagogical shifts introduced by NEP 2020, drawing on contemporary theories of early learning and best practices from global education systems. It explores the policy’s implications for curriculum design, teacher training, parental engagement, and equity in access. The article also analyzes potential challenges and opportunities in implementing these reforms and how they aim to enhance children's school readiness, cognitive development, and lifelong learning capacities.